2020
DOI: 10.1177/1176934320930263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transposable Elements in Conifer and Their Potential Application in Breeding

Abstract: Transposable elements (TEs) are known to play a role in genome evolution, gene regulation, and epigenetics, representing potential tools for genetics research in and breeding of conifers. Recently, thanks to the development of high-throughput sequencing, more conifer genomes have been reported. Using bioinformatics tools, the TEs of 3 important conifers ( Picea abies, Picea glauce, and Pinus taeda) were identified in our previous study, which provided a foundation for accelerating the use of TEs in conifer bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Responsible for major changes in the genetic architecture (e.g., rearrangements, duplication, gene breaking, and the origin of new genes) (Bennetzen, 2005; Flagel and Wendel, 2009; Lisch, 2013), TEs are usually neutral. However, such elements possess mutagenic potential due to epigenetic mechanisms and are able to alter regulatory networks and confer genetic adaptations, leading to important phenotypic variations (Lisch, 2013; Wei and Cao, 2016; Wu et al, 2020); this has currently received great attention in genetic improvement programs for several species (Domínguez et al, 2020; Lee et al, 2006; Wang et al, 2020). In Hbr, Wu et al (2020) showed that TEs located in gene regulatory regions in Hbr were involved in latex production through cis regulation, which would explain the differential gene expression among contrasting genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Responsible for major changes in the genetic architecture (e.g., rearrangements, duplication, gene breaking, and the origin of new genes) (Bennetzen, 2005; Flagel and Wendel, 2009; Lisch, 2013), TEs are usually neutral. However, such elements possess mutagenic potential due to epigenetic mechanisms and are able to alter regulatory networks and confer genetic adaptations, leading to important phenotypic variations (Lisch, 2013; Wei and Cao, 2016; Wu et al, 2020); this has currently received great attention in genetic improvement programs for several species (Domínguez et al, 2020; Lee et al, 2006; Wang et al, 2020). In Hbr, Wu et al (2020) showed that TEs located in gene regulatory regions in Hbr were involved in latex production through cis regulation, which would explain the differential gene expression among contrasting genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In rubber trees, TEs may be related to the differential expression observed in some commercial clones, affecting important processes such as rubber production (Wu et al, 2020). As pointed out by Wang et al (2020), the identification of TEs associated with functional genes related to important characteristics suggest that they can be used as molecular markers in MAS, contributing significantly to the genetic improvement of woody trees. In this sense, our findings supply a wide range of genomic resources for breeding.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, changes in methylation of transposable elements can be responsible for the variability of traits [157]. This is especially important for conifers, whose large genomes contain a high number of transposable elements, which provide vast potential genetic resources [158].…”
Section: Perspectives Of Gs In Forestrymentioning
confidence: 99%